Produksi ikan asin dengan menerapkan teknologi pengeringan berbasis energi biomassa yang ramah lingkungan untuk meningkatkan ekonomi masyarakat di Desa Buluh Cina, Kecamatan Siak Hulu, Kampar - Krisman Krisman; Erwin Erwin; Hamdi Hamdi; T Emrinaldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The potential of the economic sector of the community in the village of Buluh China, Siak Hulu Subdistrict, Kampar which has potential fisheries. The system of processing fish into salted fish products carried out through fish preservation by drying methods has long been practiced by fish preservative entrepreneurs. In particular, fish drying activities have long been a livelihood for salted fish processing communities in Buluh China village, Siak Hulu Sub-District, Kampar. However, in general, the process of preserving fish through drying methods by relying solely on sunlight is not optimal. The process of drying fish in Buluh China village, Siak Hulu Subdistrict, Kampar is still traditionally carried out, which is dried in the sun. This process takes a long time, it takes time in drying fish 2 to 4 days and that too depends on the sun. The purpose of this activity is to apply biomass-based drying technology for salted fish production. The method used is to make a dryer, biomass burning furnace, drying room (box). The results of this service show high enthusiasm from the community where salted fish production can be obtained in just 1.5 hours with temperatures in the drying chamber reaching 35 to 40 degrees Celsius.